Challenges to Shariah equity screening, from Shariah scholars' perspective. Issue 2 (19th June 2017) - Azmi, Anna; Non, Normawati; Ab Aziz, Norazlin
Abstract : Purpose: This paper aims to examine the challenges of applying Shariah law in the equity market by engaging in narratives with Shariah screeners and advisors on how they conduct their screening responsibilities despite the low levels of Islamic-related disclosure made by companies in their annual reports. The Shariah screening processes in three countries with different Islamic equity markets – Malaysia, Saudi Arabia and the United Kingdom – are examined. Design/methodology/approach: The authors interview 19 Shariah screeners and advisors in three different Islamic equity markets – Malaysia, Saudi Arabia and the United Kingdom. Findings: Overall, the findings in this study show that despite the differences in the regulatory environment, companies still make Islamic-related disclosures on a voluntary basis. However, the lack of Islamic-related disclosures presents various challenges for Shariah screeners, particularly when identifying the operations that constitute the main activity of the company in screening for prohibited activities. Research limitations/implications: Shariah screeners can play an important role in increasing the level of understanding and perhaps increasing Islamic-related disclosures in annual reports by establishing a set of effective guidelines or practices for Shariah screeners to use when screening companies for their Shariah -compliant status. Originality/value: The paper identifies a gap in the Shariah screening literature and voluntary Islamic disclosures literature. By identifying this gap, the paper highlights the challenges Shariah screeners and advisors face because of the low level of Islamic-related disclosures.